2008
DOI: 10.17305/bjbms.2008.2894
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-Lipoic Acid in Diabetic Polyneuropathy Treatment

Abstract: Diabetic neuropathy represents late diabetes complications, and diabetes duration and long-term hyperglycemia are the main reasons for polyneuropathy. The goal was to estimate the effects of alpha-lipoic acid on symptoms of diabetic neuropathy after 600 mg i.v. for 3 weeks and 3 months of 300-600 mg of alpha-lipoic acid per os. This study has been designed as a multicentric, in 5-centers in B&H, carried out by 5 physicians with 20 diabetic patients each. Following parameters were monitored in 100 diabetics suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…Glycation of laminin in ECM leads to impaired regenerative activity in diabetic neuropathy (21). Previous studies have suggested that the level of laminin mRNA increased in kidney or retina after diabetes induction (4,(22)(23)(24)(25). Our immunohistochemial results indicated that diabetes in rats resulted in significantly increased laminin expression in the perineurium, endoneurium, epineurial and endoneurial blood vessels.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Glycation of laminin in ECM leads to impaired regenerative activity in diabetic neuropathy (21). Previous studies have suggested that the level of laminin mRNA increased in kidney or retina after diabetes induction (4,(22)(23)(24)(25). Our immunohistochemial results indicated that diabetes in rats resulted in significantly increased laminin expression in the perineurium, endoneurium, epineurial and endoneurial blood vessels.…”
Section: Discussionsupporting
confidence: 48%
“…These discrepancies are probably due to differences in experimental methods, in Serafin et al study (26), mice was made diabetic with a low dose of streptozotocin with a short study time period and in Hill et al study (6), duration of diabetes in diabetic patients was different. Diabetes duration and long-term hyperglycemia are the most important reasons for polyneuropathy (22). Beneficial effect of ALA on the neuropathic symptoms due to diabetic neuropathy had been reported (10,11,13).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical hyperalgesia associated with these forms of painful peripheral neuropathy isantagonized by inhibitors of mitochondrial functions including all five mitochondrial electron transport chain complexes (Joseph and Levine, 2006), oxidative stress (Green et al, 2004; Osio et al, 2006; Vanotti et al, 2007) and generation of reactive oxygen species (ROS) (Joseph and Levine, 2010), and apoptotic signaling (Joseph and Levine, 2009). In patients, while antioxidants have been shown to have efficacy against symptoms of peripheral neuropathy associated with diabetes (Ziegler et al, 2004; Argyriou et al, 2006; Foster, 2007; Sima, 2007), complex regional pain syndrome type I and chemotherapy-induced painful neuropathy (Burekovic et al, 2008; Besse et al, 2009; Mijnhout et al, 2010; Pace et al, 2010), these effects have been relatively modest. It has been suggested that this limited efficacy is due to a failure to achieve sufficient anti-oxidant levels within the mitochondrion (Murphy and Smith, 2007), the major site of ROS generation (Inoue et al, 2003; Brand, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies are probably due to differences in experimental methods, in Serafin et al (2010) study, mice was made diabetic with a low dose of STZ with a short-term study and in Hill (2009) study, duration of diabetes in diabetic patients were different. Duration of diabetes and long-term hyperglycemia are the most important reasons for polyneuropathy (Bureković et al, 2008). Beneficial effects of ALA on the neuropathic symptoms due to diabetic neuropathy had been reported (Vallianou et al, 2009;Han et al, 2012;Ziegler, 2004).…”
Section: Discussionmentioning
confidence: 99%